Inovasi dalam Pengembangan Sosial Emosional Anak Usia Dini - Cici, Cici; Supriadi, Supriadi (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early childhood social-emotional development is vital in forming mentally and emotionally healthy individuals. Collaboration between educators and families is critical in creating a supportive environment for developing these social-emotional skills. This paper aims to investigate the role of cooperation between educators and families in supporting the social-emotional development of early childhood in the family and school environment. This research uses a qualitative approach by analyzing related scientific literature, case studies, and practical experiences collaborating with educators and families to support early childhood social-emotional development. The research results show that collaboration between educators and families can strengthen the social-emotional development of early childhood by providing open communication channels, providing resources and information, building solid educational partnerships, providing parenting skills training, supporting families in problem-solving, and increasing people's involvement. Old at school. This collaboration allows children to develop communication, emotional management, and other social skills more effectively, helping them grow and develop positively.